Oględziny zwłok i miejsca ich znalezienia w przypadku uduszenia gwałtownego - Dembowska, Izabela (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The author presents cases of death as a result of hanging, throttling, strangulation or suffocation presented in forensic literature. Those cases suggest murder. Only the analysis of the results of crime investigation — place of discovery of the corpse, examination of the victim and their clothes, toxicological tests — allows to determine whether death was caused by suicidal or homicidal strangulation.
Keywords: oględziny zwłok; śledztwo na miejscu zbrodni; powieszenie; uduszenie; uduszenie się